Established and novel human translational models to advance cystic fibrosis research, drug discovery, and optimize CFTR-targeting therapeutics. (June 2022) - Cholon, Deborah M.; Gentzsch, Martina
Abstract: To find a cure for cystic fibrosis, there has been tremendous progress in the development of treatments that target the basic defect in the protein channel, CFTR. However, 10% of cystic fibrosis patients have rare CFTR mutations that are still without an approved CFTR-targeting drug. To identify relevant therapies for these patients, culture models using nasal, bronchial, and rectal tissue from individual patients allow functional, biochemical, and cellular detection of drug-rescued CFTR. Additionally, novel systems such as induced pluripotent stem cell-derived models are utilized to characterize CFTR mutations and identify treatments. State-of-the-art translational models were instrumental for CFTR modulator development and may become important for gene-based drug discovery and other novel therapeutic strategies. Highlights: Relevant models of CF are critical for predicting clinical outcomes of therapeutics. Nasal, bronchial, and rectal 2D and 3D cultures have been key for drug discovery. Personalized medicine is important as individuals respond differently to drugs. Novel models such as iPSCs and organs-on-a-chip will improve drug testing. Advanced personalized models will be useful for future gene therapy drug discovery.